LEGAL CONSTRUCTION AND DISPUTE RESOLUTION OF NON-PAYMENT DEBTORS IN PAYLATER SHOPEE - Kusnaedy, Dina; Setianingrum, Reni Budi (Law Research Review Quarterly, 2024)
Shopee is the number one online shopping platform in Indonesia. Provides the Paylater feature, namely the buy now and pay later system. In the financing flow, Shopee collaborates with PT Lentera Dana Nusantara as a financing institution. Therefore, the involvement of several parties needs to be understood as well as their legal position and rights and obligations. The ease of use of this feature causes the problem of debtors who do not pay their bills. Therefore, it is necessary to analyze the efforts taken in the dispute. This study uses a statute approach with a normative juridical method. Secondary data types sourced from primary, secondary and tertiary legal materials with literature study data collection techniques and interviews with respondents that are purposive. Qualitative analysis techniques that are descriptive. The results of Shopee's Paylater research  are a form of cooperation between PT Shopee Internasional and PT Commerce Finance under the OJK which is continued by PT Lentera Dana Nusantara. The financing agreement gives rise to the regulation of the POJK Civil Code and the UUPK because there are three parties involved in the Paylater feature, namely consumers,  Shopee Paylater feature providers  and Fintech. OJK Regulation No. 10/POJK.05/2022. The systematics of using Paylater can be found out by users in the Shopee application in the Paylater menu. Default from the user's default is only in the form of payment interest. 5% of the total bill per month as a consequence of late payment. Some of the efforts made by Shopee are by freezing user accounts and making periodic payments to recording late payments in SLIK OJK. In conclusion, the need for legal protection is not only preventive legal protection but also repressive legal protection.